Training and Certification for Oil and Gas Safety Operators in Bojonegoro and Surrounding Communities - Susilo Handoko; Nugroho, Budi Sulistiyo Nugroho; Ayende; Widiyanto, Totok; Hamid, Farid Alfalaki; Indriani, Erdila; Astrie, Astrie Kusuma Dewi; Wardhana, Asepta Surya (Civitas : Jurnal Pengabdian Masyarakat, 2024)
Occupational Safety and Health (OSH) is indispensable to the oil and gas sector, which encompasses production, processing, and transportation, due to its substantial risk of workplace accidents and fires. Oil and gas OSH is a regulation that ensures the reliable operation and safety of oil and gas institutions/companies by standardizing equipment, personnel, general protocols for oil and gas installations, and operational procedures. OSH certification is a highly regarded indicator of documented expertise and is highly regarded for its credibility. The process of implementing this OSH training and certification involves the identification of training requirements, the preparation of a curriculum, and the coordination with relevant parties, specifically the Bojonegoro Regency Government. Preparation of socialization from participant registration through the selection of participants based on their basic requirements or qualifications. Theory sessions and practical sessions comprise training implementation. The theoretical session involves the delivery of material in the classroom, while the practical session involves the simulation of tool use in the fire and safety laboratory. In collaboration with LSP PPSDM Migas, the STTK certification exam for operator level was administered. The National Professional Certification Agency (BNSP) issues certificates. A total of 25 participants took the STTK exam on 8-9 August 2024, with 23 of them being declared competent and passing. The certification exam for the operator level was administered in conjunction with LSP PPSDM Migas. Furthermore, an additional examination was administered on August 27-28, 2024. Thirty-one individuals were declared competent and successfully completed the certification, out of a total of fifty.